ANTIDIABETIC EVALUATION OF ISOLATED COMPOUNDS FROM TINOSPORA CORDIFOLIA IN ALLOXON INDUCED DIABETIC RAT MODEL - Bindurani L G P, Ram; Singh, Anoop (Journal of Biomedical and Pharmaceutical Research, 2019)
Natural products with medicinal value are gradually gaining importance in clinical research due to their well-known property of no side effects as compared to synthetic drugs. Tinospora cordifolia commonly named as “Guduchi” is known for its immense application in the treatment of various diseases in the traditional Ayurveda literature. The present study was aimed to evaluate the anti-diabetic activity of isolated compounds from aerial parts of Tinospora cordifolia (Guduchi) in alloxan induced diabetic rats. Diabetic wistar albino rats were treated with standard drug Glibenclamide and prepared drug formulation in two different doses 250 mg and 500 mg/kg. Hypoglycemic effect was evaluated in these rats and the efficacy of isolated compounds was administered in alloxan induced diabetic rats. At the end of study period blood glucose level were statistically analyzed based on the results. Isolated compounds produced a significant reduction in blood glucose level when compared with non-treated diabetic rats. So the present research work was confirmed that the isolated compounds possess hypoglycemic effect significantly.